2023
DOI: 10.1038/s41598-023-32885-x
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between high-density lipoprotein cholesterol and bone mineral density in adolescents: a cross-sectional study

Abstract: Recent studies have shown a correlation between high-density lipoprotein cholesterol (HDL-C) and bone mineral density (BMD) in adults, but their relationship is unclear in adolescents. This study aimed to explore whether a correlation existed between them among adolescents aged 12–19. Data analyzed in our study was fetched from the National Health and Nutrition Examination Survey (NHANES) database 2011–2018. The relationship between HDL-C level and total BMD value was analyzed by multivariate logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the NHANES 2011–2018 data, a study conducted by Xiao et al found a negative relationship between LDL-C levels and lumbar BMD in the young- and middle-aged population [ 5 ]. Additionally, Wang's study, after accounting for all relevant covariates, revealed an interesting inverted U-shaped curve representing the correlation between HDL-C levels and total BMD among adolescents aged 16–19 [ 33 ]. Conversely, in the general population aged 20–59, HDL-C levels demonstrated a positive association with lumbar BMD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the NHANES 2011–2018 data, a study conducted by Xiao et al found a negative relationship between LDL-C levels and lumbar BMD in the young- and middle-aged population [ 5 ]. Additionally, Wang's study, after accounting for all relevant covariates, revealed an interesting inverted U-shaped curve representing the correlation between HDL-C levels and total BMD among adolescents aged 16–19 [ 33 ]. Conversely, in the general population aged 20–59, HDL-C levels demonstrated a positive association with lumbar BMD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple researches have shown conflicting outcomes. In a MIDUS study of 440 participants the authors found that elevated blood levels of HDC-L were associated with a lower bone density [ 27 ], Another cross-sectional investigation of teenagers purportedly found a negative relationship between male adolescents' total BMD and HDL-C levels [ 28 ]. Furthermore, the authors of a cross-sectional study with 13,592 participants reported no associations between BMD and total cholesterol, LDL, or HDL levels in fully adjusted models [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is a medical condition characterized by high levels of triglycerides and their associated lipoproteins in the bloodstream [ 8 , 9 ]. Nevertheless, the majority of recent studies have concentrated on examining the association between a solitary variable and BMD [ 10 , 11 ], and even the opposite results [ 12 – 14 ]. As a result, multiple clinical studies attempt to identify an osteoporosis risk marker that accurately predicts dyslipidemia [ 15 ].…”
Section: Introductionmentioning
confidence: 99%